Meta-Analysis of Mitochondrial DNA Reveals Several Population Bottlenecks during Worldwide Migrations of Cattle - Lenstra, Johannes; Ajmone-Marsan, Paolo; Beja-Pereira, Albano; Bollongino, Ruth; Bradley, Daniel; Colli, Licia; De Gaetano, Anna; Edwards, Ceiridwen; Felius, Marleen; Ferretti, Luca; Ginja, Catarina; Hristov, Peter; et al. (Diversity (Basel), 2014)
Several studies have investigated the differentiation of mitochondrial DNA in Eurasian, African and American cattle as well as archaeological bovine material. A global survey of these studies shows that haplogroup distributions are more stable in time than in space. All major migrations of cattle have shifted the haplogroup distributions considerably with a reduction of the number of haplogroups and/or an expansion of haplotypes that are rare or absent in the ancestral populations. The most extreme case is the almost exclusive colonization of Africa by the T1 haplogroup, which is rare in Southwest Asian cattle. In contrast, ancient samples invariably show continuity with present-day cattle from the same location. These findings indicate strong maternal founder effects followed by limited maternal gene flow when new territories are colonized. However, effects of adaptation to new environments may also play a role.